Art of Engagement: Visual Art of Thailand in Global Contexts - Thanom Chapakdee (IJCAS (International Journal of Creative and Arts Studies), 2016)
This paper on the topic of Art of Engagement: Visual Art of Thailand in Global Contexts, attempts to explore that “global contexts” is transformed because of the impacts rapid change in economics, politics, society and culture. Globalization based on the notion of Global art and transform Thai art scene into the state of international art movement such as Installation art, Performance art, Community art, i.e. these movement becomes the mainstream of art since 1980s. This kind of movement which artist has created the art objects, space, time and sphere as a model of sociability which audiences can participate with people in community as relational art practice. The relational art becomes the space of exchange and participants can share experienced of taste, aesthetic, criticism which it’s related to art objects and sphere of community. This paper will explains that relational art is in the process of art of engagement. That is why art has become the community engagement which art objects and practical based are of the relational art and relational aesthetics.